Priority Strategies for Improving Teachers’ Innovative Behavior using SITOREM Analysis - Dasmo Dasmo; Aceng Abdul Aziz; Septa Wati; Nurjanah Nurjanah; Lulu Hanifah Syaharani (Jurnal Pemberdayaan Masyarakat, 2026)
In the context of ongoing transformation in school learning, teachers are required to adapt and develop more innovative instructional practices continuously. This study examines the influence of technology leadership, self-efficacy, and ICT literacy on teachers’ innovative behavior and identifies priority areas for improvement using SITOREM analysis. A descriptive quantitative approach was employed, involving 136 teachers selected through multistage random sampling from private senior high schools in Depok City, West Java. Data were collected through structured questionnaires and a standardized test, and analyzed using path analysis followed by SITOREM. The results indicate that all three variables significantly influence teachers’ innovative behavior, with technology leadership emerging as the most dominant factor. Further analysis highlights several priority areas requiring attention, particularly those related to professional practice, teacher development, infrastructure support, and key aspects of self-efficacy. These findings suggest that improving innovative behavior requires not only strengthening overall competencies but also focusing on specific areas where performance remains suboptimal. The integration of statistical analysis with a priority-based approach provides more practical and targeted guidance for managing innovation in schools.